Effectiveness of portable air filtration on reducing indoor aerosol transmission: preclinical observational trials. (January 2022) - Lee, J.H.; Rounds, M.; McGain, F.; Schofield, R.; Skidmore, G.; Wadlow, I.; Kevin, K.; Stevens, A.; Marshall, C.; Irving, L.; Kainer, M.; Buising, K.; et al.
Summary: Background: While the range of possible transmission pathways of severe acute respiratory syndrome coronavirus-2 in various settings has been investigated thoroughly, most authorities have recently acknowledged the role of aerosol spread in its transmission, especially in indoor environments where ventilation is poor. Engineering controls are needed to mitigate aerosol transmission in high-risk settings including hospital wards, classrooms and offices. Aim: To assess the effectiveness of aerosol filtration by portable air cleaning devices with high-efficiency particulate air filters used in addition to a standard building heating ventilation and air conditioning (HVAC) system. Methods: Test rooms, including a single-bed hospital room, were filled with test aerosol to simulate aerosol movement. Aerosol counts were measured over time with various portable air cleaning devices and room ventilation systems to quantify the overall aerosol clearance rate. Findings: Portable air cleaning devices were very effective for removal of aerosols. The aerosols were cleared five times faster in a small control room with portable air cleaning devices than in the room with HVAC alone. The single-bed hospital room had an excellent ventilation rate (∼14 air changes per hour) and cleared the aerosols in 20 min. However, with the addition of two air cleaning devices, the clearance time was three times faster. Conclusions: Inexpensive portable air cleaning devices should be considered for small and enclosed spaces in healthcare settings, such as inpatient rooms and personal protective equipment donning/doffing stations. Portable air cleaning devices are particularly important where there is limited ability to reduce aerosol transmission with building HVAC ventilation.